FALSE HARMONY AND THE MORAL SEMIOTICS OF THE ZOMBIE IN THE INDONESIAN HORROR FILM ABADI NAN JAYA (2025) (INTERNATIONAL SEMINAR, 2025)
This paper examines the moral and cultural semiotics of zombie figures in the Indonesian horror film Abadi Nan Jaya. Utilizing qualitative, interpretive methodology rooted in film and semiotics theories of culture Studies, the study deconstructs how visual form, color and narrative syntax shape signification of moral degeneracy and spiritual disquiet. The film flips universal stereotypes of the zombie from contagion, apocalypse and dehumanization to localized signs of karma, ecological upset and unsettled moral continuity. In the latter, a scene-based analysis shows mise-en-scène and color are crucial semiotic assets; green resurfaces prominently and now signifies harmony as such and becomes an idea of fertility which gets perverted by artificial light pollution and necrotic landscapes (portrayed here as for example the burned heath), visualizing that nature must still respond to the intoxication by human arrogance. Unlike western zombie stories that wrap up in apocalypse or repentance, Abadi Nan Jaya tells a morally uncertain tale of futility where an undercurrent of imbalance runs beneath the illusion of a finished circle. The undead corpse reflects ethical remnant, containing spiritual decay rather than residing in the material grotesque. These results suggest that Indonesian horror redefines global horror codes from within its own cosmological ethos, and that it could be described as a post-spiritual horror, a horror that turns fear into morality. The analysis furthers a more general dialogue on transnational genre adaptation, visual mythmaking, and shifting moral imagination in Southeast Asian cinema.